Inner Size Effect in the Polycrystalline Metal Films of Fusible Metals - S.I. Petrushenko; S.V. Dukarov; V.N. Sukhov; I.G. Churilov (Журнал нано- та електронної фізики)
We have studied the morphology changes of the continuous polycrystalline films made of fusible metals during their heating and annealing on the substrate affected by a temperature gradient. It was found, that melting of the polycrystalline metal films with grain size distributed among the wide interval, occurred only in certain temperature range, and this range reduces with the increases of average grain size. We also have estimated the average energy of intergranular borders in the tin and lead films